Risk Factors for Acute Kidney Injury in Children: A Literature Review - Wea, Lidwina Dewiyanti (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
The incidence of acute kidney injury (AKI) in children has shown a recent increase. Several contributing factors include the emergence of new diseases such as COVID-19 and the use of nephrotoxic drugs. This literature review aims to identify the risk factors associated with AKI in pediatric populations. The method used was a literature review conducted across three databases: ScienceDirect, PubMed, and Google Scholar, using the search keywords